2015
DOI: 10.1002/bkcs.10253
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 4‐(2‐Amino)ethoxy‐3′,4′‐dihydroxychalcones and Their Antioxidant and Cytotoxic Effects on Human Tumor Cells

Abstract: Aminoethyl‐substituted chalcones 3 exhibiting potent 2,2‐diphenyl‐1‐picrylhydrazyl (DPPH) radical and superoxide anion radical scavenging activities and lipid peroxidation inhibitory activities along with cytotoxicities on four human tumor cells tested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Aminoalkyl-substituted 3,4,4′-trihydroxychalcone chalcones of type 38 ( Table 3 ) have been designed as compounds with antioxidant and anticancer properties [ 92 ]. These are related to luteolin as a ring-opened analog.…”
Section: Chemistry and Health Benefits Of Hydroxy Chalconesmentioning
confidence: 99%
“…Aminoalkyl-substituted 3,4,4′-trihydroxychalcone chalcones of type 38 ( Table 3 ) have been designed as compounds with antioxidant and anticancer properties [ 92 ]. These are related to luteolin as a ring-opened analog.…”
Section: Chemistry and Health Benefits Of Hydroxy Chalconesmentioning
confidence: 99%
“…The catechol nature of MAC 4 was a barrier to its synthesis by aldol condensation reactions. Thus, the methoxymethyl group (MOM) was required to protect the free hydroxyl groups of respective 3,4-dihydroxybenzaldehyde [41,42]. Benzylideneacetone (1) was used as starting material and three steps were necessary to synthesize MAC 4 using synthetic route B (Fig.…”
Section: Chemistrymentioning
confidence: 99%
“…It consists of two aryl rings that are linked by α,β‐unsaturated ketone bridge which allow structural modification to design novel bioactive compounds. Its simple structure, low molecular weight, synthetic chemistry, and broad pharmacological importance such as anticancer, antioxidant, antibacterial, antifungal, antiviral, and anti‐inflammatory effect have increased scientific interest in the field of drug discovery. Many studies on natural, semi‐synthetic, and synthetic chalcone analogs have reported their significant anti‐inflammatory activity that inhibit potential targets, such as prostaglandins (PGs), lipoxygenase (LOX), cyclooxygenase (COX), interleukins (IL), leukotriene D 4 (LTD 4 ), and nitric oxide synthase (NOS) …”
Section: Introductionmentioning
confidence: 99%